Norma językowa w prasie polskojęzycznej na Ukrainie (wybrane aspekty) - Krawczuk, Ałła (Postscriptum Polonistyczne, 2020)
The article characterizes contemporary Polish language newspapers in Ukraine and discusses some language features of the texts in reference to language norms that are applied in Poland. Material gathered mostly from the press but also from some other sources (questionnaires, spoken texts etc.) reveal some specific features of pragmatic language norms applied by members of the Polish community in Ukraine. The thesis is specifically on language etiquette norms and explains the different criteria used in Polish language as it is used in Poland, compared with abroad. Data gathered by the author leads to the conclusion that the Polish language etiquette norm as defined by linguists would differ significantly from the norm as defined by average Polish language speakers in Ukraine.